The Guality of Information Disclosed by the Public Administration and Its Importance for the Evaluation of the Impact of Cohesion Policy on the Socio-economic Development of Poland - Mogiła, Zbigniew; Zaleski, Janusz (Journal of Public Governance, 2010)
Th e main aim of this paper was to analyze the quality of the above-mentioned data. Th e authors carried out a comparative analysis of the National Development Plan/National Cohesion Strategy transfers presented by both the Directorate General for Regional Policy and the Department of Structural Policy Coordination of the Polish Ministry of Regional Development. Furthermore, in the case of the Ministry of Regional Development, they compared the actual transfers with earlier forecasts. Th e discrepancies between the data gathered by the Polish authorities and by theEuropean administration showed that it was necessary for them to start to cooperate in this fi eld and to improve their forecasting methods.